Effect of gillnet mesh size on catch efficiency and bycatch in the Greenlandic lumpfish (Cyclopterus lumpus) fishery - Malthe Kjølhede Ahlmann Olesen; Bent Herrmann; Rikke Petri Frandsen; Flemming R. Merkel; Cas Van Der Kaaden; Søren Post (Estuarine, Coastal and Shelf Science, 2025)

Thick-billed Murres in breeding pairs migrate and overwinter far apart but in similar photic environments - Nicholas P. Huffeldt; Manuel Ballesteros; Barbara Helm; Jannie F. Linnebjerg; Flemming R. Merkel; Anders Mosbech; Morten Frederiksen (Journal of Ornithology, 2024)
Scheduling between mates in species with long-term pair bonds can be essential for positive fitness. The annual cycle in photoperiod is the primary environmental cue used by many animals to synchronize behavior and physiology among members of a population, and animals that migrate must have similar annual schedules to ensure successful breeding. However, we know little about whether members of mated pairs in migratory species experience similar photic environments across the year, which could allow for synchronization in annual phenology. Here, we used light-based geolocation to estimate positions of mated pairs of Thick-billed Murres ( Uria lomvia , a seabird a.k.a. Brünnich’s Guillemot) which bred above the northern polar circle in Greenland. We tested the hypothesis that individuals in mated pairs occur in more similar locations and photic environments than randomly matched females and males. We found no difference in the amount of spatial separation or in the photic environment between mates and randomized heterosexual pairings. In general, the distance between females and males ranged from 1,198.5 km during August to 737.4 km during January. The sexes remained in photic environments with highly correlated photoperiods and moderately correlated times of solar noon in UTC. The spatial separation of, but similar photic environments experienced by, female and male murres regardless of pair status is probably adaptive by facilitating the synchronization of annual schedules between sexes, while allowing individuals in mated pairs the freedom to pursue the best foraging opportunities during migration and overwintering independent of their mate.

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Habitat when foraging does not explain temporal segregation by sex in a breeding seabird - Nicholas P. Huffeldt; Jannie F. Linnebjerg; Jérôme Fort; Flemming R. Merkel; Morten Frederiksen (Marine Biology, 2021)

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Inferring seabird activity budgets from leg-mounted time–depth recorders - Jannie Fries Linnebjerg; Nicholas Per Huffeldt; Knud Falk; Flemming R. Merkel; Anders Mosbech; Morten Frederiksen (Journal of Ornithology, 2014)

The diet of king eiders wintering in Nuuk, Southwest Greenland, with reference to sympatric wintering common eiders - Flemming R. Merkel; Anders Mosbech; Sarah E. Jamieson; Knud Falk (Polar Biology, 2007)

The diet of common eiders wintering in Nuuk, Southwest Greenland - Flemming R. Merkel; Sarah E. Jamieson; Knud Falk; Anders Mosbech (Polar Biology, 2006)

Endogenous reserve dynamics of northern common eiders wintering in Greenland - Sarah E. Jamieson; H. Grant Gilchrist; Flemming R. Merkel; Antony W. Diamond; Knud Falk (Polar Biology, 2006)